PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN MELALUI KEPUASAAN KERJA SEBAGAI VARIABEL MEDIASI PADA PERUMDA AIR MINUMTIRTA SANJIWANI DI KABUPATEN GIANYAR - Cokorda Istri Agung Vera Nindia Putri; Tjokorda Gde Agung Wijaya Kesuma Suryawan; Octavianus Sumardana Pratama; Ni Kadek Rika Damayanti (JUIMA : JURNAL ILMU MANAJEMEN, 2025)
Employee performance is the result of a person's achievements to be able to measure an employee's performance and ability to support an organization in achieving its goals. Transformational Leadership is a variable that influences employee performance and job satisfaction is a variable that indirectly influences the relationship between transformational leadership and employee performance. There is attention and problems found related to Transformational Leadership and job satisfaction in an effort to improve employee performance at the Tirta Sanjiwani Drinking Water Company in Gianyar Regency. The formulation of the problem in this research is whether job satisfaction plays a role in mediating the relationship between transformational leadership and employee performance at the Tirta Sanjiwani Drinking Water Company in Gianyar Regency. This research aims to determine the role of job satisfaction in mediating the relationship between transformational leadership and employee performance at the Tirta Sanjiwani Drinking Water Company in Gianyar Regency. The number of samples was determined using the saturated sample method of 100 non-PNS employees at the Tirta Sanjiwani Drinking Water Company in Gianyar Regency. Data analyzed using Smart PLS includes three stages, namely outer model analysis, inner model and hypothesis testing. The results of the research show that transformational leadership has a positive and significant effect on employee performance, transformational leadership has a positive and significant effect on job satisfaction, job satisfaction has a positive but not significant effect on employee performance, job satisfaction is unable to mediate the effect of transformational leadership on employee performance at the Tirta Water Company Sanjiwani in Gianyar Regency.